SUBTITLING STRATEGIES FROM ENGLISH TO INDONESIAN IN THE IMITATION GAME MOVIE BY LEBAH GANTENG - Asrima Asrima; Serliah Nur (UIN Raden Mas Said Surakarta, 2023)
This article discusses subtitling strategies taken by Lebah Ganteng in the Indonesian subtitle of the movie entitled The Imitation Game. The aims of this research were to describe how various subtitling strategies are applied in giving the subtitles to the movie from English into Indonesian and to find out the distribution of the strategies used from the most frequent to the least. This research applied a descriptive-qualitative method. The data were analyzed based on Gottlieb’s subtitling strategies theory. The finding shows that there are eight of the total ten subtitling strategies are applied. Transfer takes 24% of the total, followed by deletion (23%), paraphrase (17%), imitation (11%), condensation (9%), expansion (9%), decimation (6%), and transcription (1%). Two strategies left unapplied are dislocation and resignation. From the comparison, It can be concluded that transfer is the dominant strategy used in the subtitling process of the movie.